Systematic benchmarking of omics computational tools - Serghei Mangul (Nature Portfolio, 2019)
Benchmarking studies are important for comprehensively understanding and evaluating different computational omics methods. Here, the authors review practices from 25 recent studies and propose principles to improve the quality of benchmarking studies.